2016
DOI: 10.1038/ejhg.2015.272
|View full text |Cite
|
Sign up to set email alerts
|

Rare variant associations with waist-to-hip ratio in European-American and African-American women from the NHLBI-Exome Sequencing Project

Abstract: Waist-to-hip ratio (WHR), a relative comparison of waist and hip circumferences, is an easily accessible measurement of body fat distribution, in particular central abdominal fat. A high WHR indicates more intra-abdominal fat deposition and is an established risk factor for cardiovascular disease and type 2 diabetes. Recent genome-wide association studies have identified numerous common genetic loci influencing WHR, but the contributions of rare variants have not been previously reported. We investigated rare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Second, the discovery and characterization of genetic variants was conducted in a large data set but was limited to individuals of European ancestry. While the genetic determinants of anthropometric phenotypes may be partly shared across different ethnicities, further investigations in other populations and ethnicities will be required for a complete understanding of the genetic relationships between body shape and cardiometabolic risk. Third, this study was largely based on population-based cohorts, the participants of which are usually healthier than the general population, and used analytical approaches that deliberately minimized the influence of outliers, in this case people with extreme fat distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the discovery and characterization of genetic variants was conducted in a large data set but was limited to individuals of European ancestry. While the genetic determinants of anthropometric phenotypes may be partly shared across different ethnicities, further investigations in other populations and ethnicities will be required for a complete understanding of the genetic relationships between body shape and cardiometabolic risk. Third, this study was largely based on population-based cohorts, the participants of which are usually healthier than the general population, and used analytical approaches that deliberately minimized the influence of outliers, in this case people with extreme fat distribution.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have connected rare genetic variation to fat distribution. An early sequencing study performed in women reported rare variants in IKBKB associating with waist-to-hip ratio (WHR) 14 . Rare variants in PDE3B and ACVR1C have been reported to associate with WHRadjBMI and related traits 9 , 10 , 13 and an exome array study of WHRadjBMI reported several novel rare variant associations 15 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study revealed that the genetic loci including COBLL1 that is strongly associated with body fat percentage showed distinct cross‐phenotype association signatures with a range of cardiometabolic traits 37 . Aggregation of rare variants in COBLL1 is associated with higher waist‐to‐hip ratio in European‐Americans, which is an established risk factor for cardiovascular disease 38 …”
Section: Discussionmentioning
confidence: 99%